2020
DOI: 10.3389/fneur.2020.00938
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors Associated With Poor Outcome in Posterior Reversible Encephalopathy Syndrome After Treatment in Children: Systematic Review and Meta-Analysis

Abstract: Objective: Chemotherapy and hematopoietic stem cell transplantation (HSCT) play important roles in clinical etiology, symptoms, signs, imaging findings, and biochemical parameters for inducing posterior reversible encephalopathy syndrome (PRES) in pediatric oncologic diseases. We aimed to evaluate various risk factors of pediatric oncologic diseases after conducting chemotherapy and HSCT to induce PRES for predicting the clinical prognosis frequency. Methods: The literature was performed on PubMed, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 59 publications
(105 reference statements)
0
6
1
Order By: Relevance
“…(4) Some of the included case series had insufficient patient information, corresponding to a low level of evidence. (5) In our previous study, we identified several factors associated with a poor outcome for PRES in pediatric oncologic/hematologic diseases ( 10 ); however, the random-effects model in the present study identified only 2 of these factors (hypertension and blood transfusion) as being significantly associated with PRES, indicating low concordance between the findings of the 2 studies.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…(4) Some of the included case series had insufficient patient information, corresponding to a low level of evidence. (5) In our previous study, we identified several factors associated with a poor outcome for PRES in pediatric oncologic/hematologic diseases ( 10 ); however, the random-effects model in the present study identified only 2 of these factors (hypertension and blood transfusion) as being significantly associated with PRES, indicating low concordance between the findings of the 2 studies.…”
Section: Discussioncontrasting
confidence: 62%
“…Although the exact cause of PRES is not known, it is thought to be related to the production of toxins induced by HSCT and chemotherapy that target capillary endothelial cells, leading to the failure of cerebral blood pressure autoregulation, endothelial dysfunction, and vasogenic edema ( 52 , 97 ). PRES is usually observed in the context of acute hypertension (sometimes treatment-induced) ( 10 12 , 15 , 17 19 , 22 28 , 32 , 33 , 44 , 46 , 47 , 57 , 65 , 98 105 ), and may be overlooked in patients with near-normal blood pressure at symptom onset ( 98 100 ). Hypertension is more common in children than in adults with PRES ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations